Transcriptomic Evidence of the Immune Response Activation in Individuals With Limb Girdle Muscular Dystrophy Dominant 2 (LGMDD2) Contributes to Resistance to HIV-1 Infection - Diez-Fuertes, Francisco; López-Huertas, María Rosa; García-Pérez, Javier; Calonge, Esther; Bermejo, Mercedes; Mateos, Elena; Martí, Pilar; Muelas, Nuria; Vílchez, Juan Jesús; Coiras, Mayte; Alcamí, José; Rodríguez-Mora, Sara (Frontiers in Cell and Developmental Biology, 2022)
LGMDD2 is a rare form of muscular dystrophy characterized by one of the three heterozygous deletions described within the TNPO3 gene that result in the addition of a 15-amino acid tail in the C-terminus.TNPO3 is involved in the nuclear import of splicing factors and acts as a host cofactor for HIV-1 infection by mechanisms not yet deciphered. . Further characterization of the crosstalk between HIV-1 infection and LGMDD2 disease may contribute to a better understanding of both the cellular alterations occurring in LGMDD2 patients and the role of TNPO3 in the HIV-1 cycle. To this regard, transcriptome profiling of PBMCs from LGMDD2 patients carrying the deletion c.2771delA in the TNPO3 gene was compared to healthy controls. A total of 545 differentially expressed genes were detected between LGMDD2 patients and healthy controls, with a high representation of G protein-coupled receptor binding chemokines and metallopeptidases among the most upregulated genes in LGMDD2 patients . Plasma levels of IFN-β and IFN-γ were 4.7- and 2.7-fold higher in LGMDD2 patients , respectively. An increase of 2.3-fold in the expression of the interferon-stimulated gene MxA was observed in activated PBMCs from LGMDD2 patients after ex vivo HIV-1 pseudovirus infection. Thus, the analysis suggests a pro-inflammatory state in LGMDD2 patients also described for other muscular dystrophies, that is characterized by the alteration of IL-17 signaling pathway and the consequent increase of metallopeptidases activity and TNF response. In summary, the increase in interferons and inflammatory mediators suggests an antiviral environment and resistance to HIV-1 infection but that could also impair muscular function in LGMDD2 patients, worsening disease evolution. Biomarkers of disease progression and therapeutic strategies based on these genes and mechanisms should be further investigated for this type of muscular dystrophy.